Juridical Analysis of Flood Disaster Management and the Role of the Community in the Villa Patumbak Permai Housing Complex, Jalan Pelajar Marindal 1, Patumbak District, Deli Serdang Regency - Dewi Robiyanti (Master of Law Program, Ekasakti University, 2026)
The flood disaster that hit the Villa Patumbak Permai Housing Complex, Jalan Siswa Marindal 1, Patumbak District, Deli Serdang Regency, had a significant impact on the social and economic life of residents. This study aims to analyze the juridical aspects of flood disaster management in the location and examine the role of the community in post-disaster mitigation and recovery. The research method used is normative and empirical juridical, with primary data in the form of field documentation and direct observation, and secondary data in the form of laws and regulations related to disaster management (Law Number 24 of 2007). The results show that despite the regulation, its implementation in the field still faces challenges, especially in terms of response speed and long-term recovery. However, the very active role of the community, as evidenced by the existence of the Citizen Post and solidarity in distributing aid and mutual cooperation to clean up the environment, is a crucial factor in reducing the impact of disasters. This study concludes that synergy between disaster management law enforcement and active community participation is needed to create regional resilience to disasters.